2020
DOI: 10.1155/2020/9389720
|View full text |Cite
|
Sign up to set email alerts
|

Association of Circulating Omentin-1 with Osteoporosis in a Chinese Type 2 Diabetic Population

Abstract: Aims. Omentin-1, a newly identified adipokine, has been demonstrated to be associated with bone metabolism, but the results have been inconsistent. Moreover, the potential relationship of circulating omentin-1 with diabetic osteoporosis has never been reported. This study is intended for studying the association between circulating omentin-1, bone mineral density (BMD), prior fragility fractures, and other bone metabolic-related parameters. Methods. Circulating omentin-1 levels were measured in 172 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…22 Patients were then classified as having DN if they had an eGFR < 60 mL/min/1.73m 2 and/or an ACR > 30 mg/g. 23…”
Section: Clinical and Biochemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Patients were then classified as having DN if they had an eGFR < 60 mL/min/1.73m 2 and/or an ACR > 30 mg/g. 23…”
Section: Clinical and Biochemical Measurementsmentioning
confidence: 99%
“…Patients were diagnosed as having PAD if an ABI value <0.9 on either limb. 23 DFU was defined as a full-thickness wound (penetrates dermal tissues) below the ankle in a person with diabetes caused by peripheral neuropathy or ischaemia or both, and consequent trauma to the foot. 41 A Canon CR-2 Digital Retinal Camera was performed to obtain two-field fundus photography of patient's eyes (Canon Inc., Kanagawa, Japan).…”
Section: Assessment and Diagnostic Criteria Of Dpnmentioning
confidence: 99%
“…Thus, omentin-1 is a candidate surrogate serum marker for diabetic OP among females. Further, multivariate analysis showed plasma omentin-1 to be an independent, decisive factor for OP in women exclusively ( 34 ).…”
Section: Introductionmentioning
confidence: 96%
“…Several studies showed that high omentin-1 protected from osteoporosis by suppressing bone resorption and promoting bone formation in mice [9]. Other studies showed that serum levels of omentin-1 were negatively correlated with bone mineral density (BMD) and bone turnover markers through inhibiting bone formation in diabetic osteoporosis and postmenopausal women [10], others showed that omentin-1 has no effect on bone metabolism [11]. Nonetheless, the osteogenic outcome induced by omentin-1 remains uncertain [12].…”
Section: Introductionmentioning
confidence: 99%